Harnessing aquatic plant growth forms to apply European nutrient‐enrichment bioindicators to Canadian waters. (27th July 2022) - Tyrrell, Christopher D.; Chambers, Patricia A.; Culp, Joseph M.
Abstract: Premise: Aquatic macrophyte species abundance and nutrient affinity are used in metrics to assess the trophic condition of lakes and rivers. The development of these indices is often regional, with inter‐regional comparisons being complicated by the lack of taxonomic overlap. Here, we use a traits‐based approach to expand the geographic scope of existing metrics. Methods: We generalized European trophic affinity values using the response of plant growth form to the light–nutrient gradient, then applied these values to sites in Canada. We evaluated the method's performance against the measured total phosphorus concentration (TP). Results: Free‐floating and emergent growth forms were associated with enriched waters (>0.2 mg/L TP), whereas rosette forms were associated with oligotrophic conditions (<0.05 mg/L TP). The responses were longitudinally consistent, and the site scores among indices were highly collinear. Growth form–based scores were more strongly correlated with TP than were species‐based scores (0.42–0.56 versus 0.008–0.25). Discussion: We leveraged the ecological relationship between increased surface water nutrient enrichment and the dominance of particular aquatic plant growth forms to generalize aquatic plant trophic indices. We demonstrated an approach for adapting species‐based indices to plant traits to facilitate a broader geographic application and simpler data collection, which could be used to develop an easily applied trait‐based method of assessing water nutrient status.